Aplicación web e-commerce B2C para ventas, créditos e inventarios del MAG de Morona Santiago utilizando la metodología ágil Kanban - Andino Santana, Jimson Sebastian (2025)
This research focused on the development of a B2C e-commerce web application for the Ministry of Agriculture and Livestock of Morona Santiago. The objective was to create a virtual store showcasing the physical products sold at the Amazonian fair, enabling their acquisition in a more efficient and timely manner. The project utilised various technologies, including Visual Studio Code as the development environment, Node.js and MySQL for the backend, React.js for the frontend, XAMPP as the database server, and Express JS for web server support. The application was built following the MVC (Model-View-Controller) architecture and employed the agile Kanban methodology to manage the development process. This approach effectively organised the workflow and allowed for adaptation to evolving requirements. A quantitative approach was adopted to evaluate the usability of the web application, adhering to the guidelines of the ISO 9241-11 standard. The results were highly positive in terms of efficiency, effectiveness, and user satisfaction. In terms of efficiency, users perceived the system as highly efficient, achieving an average score of 95.91%. This was evident in the speed and smoothness with which they completed assigned tasks without complications. Regarding effectiveness, a 97.22% success rate was recorded in task completion, highlighting the system's ability to meet user objectives effectively. Finally, the usability assessment using the System Usability Scale (SUS) yielded a score of 94.08%, placing the application in the "best imaginable usability" category. This result demonstrated a high level of satisfaction among users interacting with the system.